2019
DOI: 10.1111/jocs.14044
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency ventilation during cardiopulmonary bypass for lung protection: A randomized controlled trial

Abstract: Objective: Pulmonary dysfunction is a common complication in patients undergoing heart surgery. Current clinical practice does not include any specific strategy for lung protection. To compare the anti-inflammatory effects of low-frequency ventilation (LFV), as measured by nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) p65 pathway activation, for the entire cardiopulmonary bypass (CPB) vs both lungs left collapsed in patients undergoing coronary artery bypass grafting (CABG).Methods: Two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Although studies have demonstrated that atelectasis and infection are reduced with low tidal volume ventilation [ 10 , 11 ] , we did not find such a difference in our ventilation and non-ventilation groups. Similar to our study, Fiorentino et al [ 12 ] did not find any difference between the TNF-α, IL-1β, IL-18, IL-6, IP-10, CXCL-8 and IL-10 levels of patients that did and did not receive ventilation support. An animal study supported these findings by reporting that IL-6, IL-8 and IL-10 levels were similar in all subject groups [ 7 ] .…”
Section: Discussionsupporting
confidence: 91%
“…Although studies have demonstrated that atelectasis and infection are reduced with low tidal volume ventilation [ 10 , 11 ] , we did not find such a difference in our ventilation and non-ventilation groups. Similar to our study, Fiorentino et al [ 12 ] did not find any difference between the TNF-α, IL-1β, IL-18, IL-6, IP-10, CXCL-8 and IL-10 levels of patients that did and did not receive ventilation support. An animal study supported these findings by reporting that IL-6, IL-8 and IL-10 levels were similar in all subject groups [ 7 ] .…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, we applaud Fiorentino et al for their important contribution. Far from being a denouement, these reported results raise very important questions.…”
mentioning
confidence: 61%
“…Fiorentino et al present the readers with the results of their randomized controlled trial relating the effects of low frequency ventilation (LFV) on the pulmonary inflammatory pathways and indices of gas exchange. To their surprise, they observed no significant differences in outcomes between the cohort of interest (patients ventilated with air during CPB at 6 to 8 mL/kg, 5 breaths/minute, and zero end‐expiratory pressure) and the controls (patients whose lungs were disconnected from the breathing circuit and remained collapsed for the duration of CPB).…”
mentioning
confidence: 99%
“…Furthermore, bronchial blood flow is reduced due 15 to haemodynamic and pulsatility changes during bypass and changes in vascular 16 resistances. These atelectatic and ischemic changes may promote tissue hypoxia, 17 oxidative stress and lung cellular damage [3][4][5][6]. Towards the end of CPB, full 18 ventilation is recommenced and pulmonary blood flow is restored with potential 19 injury by reperfusion including oxidative stress [7,8], and inflammatory cell 20 infiltration [9].…”
mentioning
confidence: 99%